If you're a monster and you know it - Emberley, Rebecca; Emberley, Ed (New York : Orchard Books, 2010)
Monsters sing their own version of this popular song that encourages everyone to express their happiness through voice and movement
Includes a free, downloadable copy of the song "If you're a monster and you know it," performed by Adrian Emberley
ages 3-5
Keywords: Children's songs -- Texts; Monsters -- Songs and music; Picture books